Tinjauan Konseptual Nilai-nilai Pancasila sebagai Landasan Fundamental Karakter Kewirausahaan dalam Pendidikan Pancasila - Alif Lukmanul Hakim (Jayapangus Press, 2026)
This research aims to conceptually examine the values of Pancasila as the basis for ethics in the formation of entrepreneurial ethics through Civic Education. In the midst of global challenges and disruptive digitalization in Indonesian society today, it is crucial to project that entrepreneurial activities should not only focus on fiscal aspects but also be rooted in noble national values. This study uses library research with a descriptive qualitative approach by reviewing scientific literature, policy documents, and relevant previous studies. The results show that the values of Pancasila, particularly social justice, togetherness, and shared responsibility, play an important role as an ethical foundation in shaping an entrepreneurial character oriented towards economic sustainability. In addition, this study also formulates an integrative model that makes Civic Education a reference in internalizing Pancasila values into entrepreneurial character. This reseacrh contributes to the development of an integrative conceptual framework that correlates Pancasila, Civic Education, and entrepreneurship as a reference for curriculum development.